IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI PT CANNET ELEKTRIK - Fejri Subriadi; Anis Hoerunnisa (Politeknik ATI Padang, 2019)
Occupational Safety and Health Management System, referred to as SMK3, is part of the overall company management system in the context of controlling risks related to work activities in order to create a safe, comfortable, efficient and productive workplace. Occupational Safety and Health, hereinafter abbreviated to K3, are all activities to guarantee and protect the safety and health of workers through the prevention of work accidents and occupational diseases. The research method used is quantitative descriptive. From the analysis that has been done that the implementation of SMK3 in PT Cannet Elektrik Indonesia has the value of implementation of SMK3 included in both categories with a value of 82.8%. For work accidents at PT Cannet Elektrik Indonesia from 2014-2019 there were 12 work accidents including 11 times (91.6%) minor injuries and 1 (8.3%) moderate injuries.